Narratives and marginalised voices: storying the sport and physical activity experiences of care-experienced young people. Issue 3 (4th May 2021) - Quarmby, Thomas; Sandford, Rachel; Hooper, Oliver; Duncombe, Rebecca
ABSTRACT: Existing research has so far failed to provide opportunities for the stories of care-experienced young people to be heard, especially regarding their perspectives on sport and physical activity. As such, a key aim of this paper was to showcase the stories of three care-experienced individuals; stories that focus specifically on the role of sport and physical activity in their lives and highlight the complexities of being in care and the challenges they can encounter in this respect. In drawing on the creative analytic practice of creative non-fiction, and adopting the position of the storyteller, we seek to present three stories from individuals who each experienced care in their youth but have now left the care system. We argue that these stories can act as valuable pedagogical resources through which the reader can enter into the lived realities of care-experienced young people and better understand how they experience and manage challenging conditions and events. Moreover, in presenting the articulate reflections of these three care-leavers, they serve to offer a counter narrative to the dominant discourse of care-experienced young people as troublesome and uneducated, showcasing instead the nuanced lives they each have to navigate.